ANALISIS KEBUTUHAN PENGEMBANGAN LKPD DIGITAL UNTUK PEMBELAJARAN IPS KELAS 5 DI SD - Shavira Nur Annisa; Usman, Herlina; Yunus, Mahmud (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the needs in developing a digital Student Worksheet (LKPD) based on Canva for Social Studies (IPS) learning in fifth-grade elementary school. The background of this study lies in the continued use of conventional worksheets, which are considered visually unappealing and less effective in encouraging student engagement, leading to decreased learning motivation. A qualitative approach was employed using in-depth interview techniques with teachers and students at SDN Mekarjaya 20, Depok City, as the research subjects. The results show that teachers require more interactive and contextually relevant instructional media, particularly for Social Studies subjects. On the other hand, students expressed interest in digital learning media that are visually appealing and more flexible to access. Based on these findings, it can be concluded that the development of a Canva-based digital LKPD is feasible to proceed to the design and development stages in order to enhance the effectiveness of Social Studies learning for fifth-grade elementary students.